Legitimising Inter-Sectoral Public Health Policies: A Challenge for Professional Identities? - Ellen Strøm Synnevåg; Roar Amdam; Elisabeth Fosse (International Journal of Integrated Care, 2019)
Introduction: The 2012 Norwegian Public Health Act stipulates that all Norwegian municipalities need to integrate public health concerns in their decision-making processes at all policy levels. Based on a Health in All Policies (HiAP) approach, population health and health equity are seen as whole-of-government responsibilities, making all municipal actors across sectors and professional boundaries responsible for health issues. Although many municipalities are well on their way towards implementing this goal, several experience a lack of legitimacy and inter-sectoral collaboration, as well as encounter conflicting professional identities. Theory and Methods: In this interview-based case study, we investigate the legitimacy of the HiAP approach in three Norwegian municipalities. We use an institutional perspective to analyse legitimacy, and we discuss how professional identities might relate to the implementation of this inter-sectoral collaboration. Results: Our findings suggest that the three municipalities are in the process of legitimising HiAP. Further, that legitimacy based on the integration of HiAP in planning and management structures and in formal documents seems easier or less complicated to achieve than other types of legitimacy related to personal understanding, values and norms. Conclusions and discussion: We argue that these findings may be related to the possible risk of identity conflicts, which could potentially pose challenges to collaborations, such as HiAP, and then again challenge the implementation of integrated care.